In vitro conservation and low cost micropropagation of Cochlospermum regium (Mart. Ex. Scharank) - Inácio, Marielle Cascaes [UNESP]; Bertoni, Bianca Waléria; França, Suzelei de Castro; Pereira, Ana Maria Soares [UNESP] (My University, 2011)
Cochlospermum regium (Mart. Ex. Scharank), a Cochlospermaceae is a Cerrado medicinal species showing antimicrobial activity on the female reproductive system. The species risks being genetically eroded since it is highly explored, the biome devastated and the plant roots are employed for phytotherapeutic preparations. This study aims to develop a micropropagation protocol for large scale production of plantlets and establish the species conservation in a germplasm bank, in vitro. Nodal segments were inoculated into Murashige and Skoog (MS) medium supplemented with different concentrations of sucrose, BAP, kinetin, zeatin, Phytagel ® and activated charcoal. The bud position effect on the multiplication index was evaluated and the auxin IBA utilized in rooting experiments. The best multiplication response was with the apical bud in culture medium in absence of cytokinins. MS inoculated explants with different IBA concentrations did not root in vitro, but ex vitro rooting was satisfactory. Survival of explants, 47.62%, was for 4 months in germplasm bank conditions without culture medium transference. © 2011 Academic Journals.
Keywords: algodãozinho do campo; Cerrado; Cochlospermaceae; Medicinal plants; Plant growth regulators